In Vivo Biocompatibility Study on Functional Nanostructures Containing Bioactive Glass and Plant Extracts for Implantology - Floroian Laura, Badea Mihaela (My University, 2024)
In this paper, the in vivo behavior of orthopedic implants covered with thin films obtained by matrix-assisted pulsed laser evaporation and containing bioactive glass, a polymer, and natural plant extract was evaluated. In vivo testing was performed by carrying out a study on guinea pigs who had coated metallic screws inserted in them and also controls, following the regulations of European laws regarding the use of animals in scientific studies. After 26 weeks from implantation, the guinea pigs were subjected to X-ray analyses to observe the evolution of osteointegration over time; the guinea pigs’ blood was collected for the detection of enzymatic activity and to measure values for urea, creatinine, blood glucose, alkaline phosphatase, pancreatic amylase, total protein, and glutamate pyruvate transaminase to see the extent to which the body was affected by the introduction of the implant. Moreover, a histopathological assessment of the following vital organs was carried out: heart, brain, liver, and spleen. We also assessed implanted bone with adjacent tissue. Our studies did not find significant variations in biochemical and histological results compared to the control group or significant adverse effects caused by the implant coating in terms of tissue compatibility, inflammatory reactions, and systemic effects.
Keywords: in vivo study; plant extract; orthopedic implant